Dukungan Sosial Tenaga Kesehatan saat Menghadapi Pandemi Covid–19 terhadap Tingkat Stres yang Dialami di Kota Magelang - Moh. Hanafi; Heru Supriyatno; Dwi Ari Murti Widigdo (Poltekkes Kemenkes Bengkulu, 2023)
The impact of the Covid-19 pandemic is extensive on people's lives, including healthcare workers, whose families, friends, and close ones are crucial in providing support to help them reduce stress. The aim of this research is to identify the relationship between social support and stress levels among healthcare workers during the Covid-19 pandemic in Magelang City. A quantitative research design with a cross-sectional approach was used, involving 127 respondents. The Multidimensional Scale of Perceived Social Support (MSPSS) and the Perceived Stress Scale (PSS) were used to collect data. The research results indicate that the majority of respondents experienced high social support, with 111 individuals (87.4%), and the majority of respondents experienced moderate levels of stress, with 72 individuals (56.7%). The correlation test results showed a significant value with a p-value of 0.01 (p<0.05) and a correlation coefficient of -0.228. These results indicate a negative relationship between social support and stress levels, where higher levels of social support are associated with lower levels of stress experienced by the respondents. This research also demonstrates a relationship between the level of social support and stress levels among healthcare workers. Therefore, structured social support is necessary for healthcare professionals affected by the Covid-19 pandemic, with a focus on enhancing individual resilience through counseling within clinical supervision.